The status of the Hungarian Merino sheep breed compared to the other merino breeds - Szabó, Mária; Kusza, Szilvia; Csízi, István; Monori, István (Acta Agraria Debreceniensis, 2016)
Merino and Merino-derived sheep breeds have been widely known and distributed across the world, both as purebred and admixed populations. They represent a diverse genetic resource which over time has been used as the basis for the development of new breeds. In spite of this, their gene-pool potential is still unexplored. The Merino sheep represent the most important sheep resource of the Hungarian husbandry. It has the largest amount of individuals between both of the stock and commercial flocks. But in Europe the Merino stocks went through a drastic reduction in number. Thus these breeds became endangered in several countries as well as in Hungary. In this study we would like to present the recent status of different Merino breeds of the world to ground our further phylogenetic research with the Hungarian Merino breed.